1,25-Dihydroxyvitamin D(3) Inhibits the Differentiation and Migration of T(H)17 Cells to Protect against Experimental Autoimmune Encephalomyelitis - Chang, Jae-Hoon (Public Library of Science, 2010)
BACKGROUND: Vitamin D(3), the most physiologically relevant form of vitamin D, is an essential organic compound that has been shown to have a crucial effect on the immune responses. Vitamin D(3) ameliorates the onset of the experimental autoimmune encephalomyelitis (EAE); however, the direct effect of vitamin D(3) on T cells is largely unknown. METHODOLOGY/PRINCIPAL FINDINGS: In an in vitro system using cells from mice, the active form of vitamin D(3) (1,25-dihydroxyvitamin D(3)) suppresses both interleukin (IL)-17-producing T cells (T(H)17) and regulatory T cells (Treg) differentiation via a vitamin D receptor signal. The ability of 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) to reduce the amount of IL-2 regulates the generation of Treg cells, but not T(H)17 cells. Under T(H)17-polarizing conditions, 1,25(OH)(2)D(3) helps to increase the numbers of IL-10-producing T cells, but 1,25(OH)(2)D(3)'s negative regulation of T(H)17 development is still defined in the IL-10(−/−) T cells. Although the STAT1 signal reciprocally affects the secretion of IL-10 and IL-17, 1,25(OH)(2)D(3) inhibits IL-17 production in STAT1(−/−) T cells. Most interestingly, 1,25(OH)(2)D(3) negatively regulates CCR6 expression which might be essential for T(H)17 cells to enter the central nervous system and initiate EAE. CONCLUSIONS/SIGNIFICANCE: Our present results in an experimental murine model suggest that 1,25(OH)(2)D(3) can directly regulate T cell differentiation and could be applied in preventive and therapeutic strategies for T(H)17-mediated autoimmune diseases.